2020
DOI: 10.3390/ncrna7010001
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs in Diffuse Large B-Cell Lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common lymphoid malignancy in adults. Although significant progress has been made in recent years to treat DLBCL patients, 30%–40% of the patients eventually relapse or are refractory to first line treatment, calling for better therapeutic strategies for DLBCL. Long non-coding RNAs (lncRNAs) have emerged as a highly diverse group of non-protein coding transcripts with intriguing molecular functions in human disease, including cancer. Here, we review the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…However, the IPI systems do not consider factors inherent to the molecular heterogeneity of patients, leading to the critical need of identifying additional molecular prognostic biomarkers. In the last decade, several studies have demonstrated the contribution of miRNAs to lymphoma development, implying their potential as novel biomarkers in cancer diagnosis and prognosis [ 14 ]. More recently, a new class of ncRNA, the lncRNAs, has emerged also as important regulators of gene expression, and their deregulation has been implicated in the initiation and progression of cancer, showing great potential as predictive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the IPI systems do not consider factors inherent to the molecular heterogeneity of patients, leading to the critical need of identifying additional molecular prognostic biomarkers. In the last decade, several studies have demonstrated the contribution of miRNAs to lymphoma development, implying their potential as novel biomarkers in cancer diagnosis and prognosis [ 14 ]. More recently, a new class of ncRNA, the lncRNAs, has emerged also as important regulators of gene expression, and their deregulation has been implicated in the initiation and progression of cancer, showing great potential as predictive biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of hsa-hsa-miR-27a, hsa-hsa-miR-142, hsa-miR-199b, hsa-miR-222, hsa-miR-302, hsa-miR-330, hsa-miR-425, and hsa-miR-519 seemed to be associated with OS of R-CHOP treated patients with DLBCL [ 13 ]. Recently, lncRNAs have emerged as a new level of gene expression regulation, playing an important role in lymphoma development [ 14 ]. LncRNAs are >200 nt long transcripts with no protein-coding capacity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using RNA sequencing, Karstensen et al analyzed the transcription profile of rituximab-sensitive and resistant DLBCL cell lines. They observed a differential expression of lncRNA between sensitive and resistant cells, comprising 54 up and 69 downregulated lncRNAs [ 154 ]. In MCL cells, a study by Mourtada-Maarabouni et al demonstrated that lncRNA GAS5 regulates the effect of known mTOR inhibitors, such as rapamycin, everolimus, and temsirolimus.…”
Section: Mirnas and Lncrnas As Potential Biomarkers For Nhlmentioning
confidence: 99%
“…Long non-coding RNA also plays a vital role in the occurrence, progression, resistance, and prognosis of DLBCL [21][22][23] . LINC00857 can promote the occurrence and progression of DLBCL 24 .…”
Section: Introductionmentioning
confidence: 99%